Beginning Reading Skills Through Syllable Method with Word Tree Media: Keterampilan Membaca Permulaan dengan Metode Suku Kata dan Media Pohon Kata - Fadila, Syahmila; Guswita, Reni; Sundahry (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Reading ability is a fundamental skill that underpins students’ overall learning success, yet many early grade learners still face obstacles in achieving fluency. Specific background: In Indonesian elementary schools, conventional reading practices often lack variation in methods and media, limiting student engagement and comprehension. Knowledge gap: Few studies have systematically integrated the syllable method with interactive media tailored to strengthen beginning reading skills. Aims: This study seeks to examine the effectiveness of the Syllable Method assisted by Word Tree Media in improving the beginning reading skills of second-grade students at SDN 112/II Purwo Bakti. Results: Conducted as classroom action research over two cycles, the study recorded progressive improvements in teacher observation scores (65% to 80%), student observation scores (59.66% to 80%), and reading mastery (from 6 to 28 out of 30 students meeting the minimum competency standard). Novelty: Unlike prior approaches, the integration of syllable-based instruction with Word Tree Media offers both visual scaffolding and interactive engagement, fostering active participation and systematic reading development. Implications: The findings suggest that this method can be adopted by teachers as a practical, low-cost innovation to enhance literacy instruction and may be further explored across grade levels and subjects. Highlight: The syllable method assisted by word tree media enhances early reading skills. Findings reveal significant improvements in teacher performance, student engagement, and reading mastery. This simple and interactive medium provides an innovative alternative for early literacy instruction. Keywords: Beginning Reading, Syllable Method, Word Tree Media, Literacy, Elementary Education